ANALISIS AUDIT INVESTIGATIF DALAM PENGUNGKAPAN FRAUD PADA TRANSFORMASI TEKNOLOGI DIGITAL DI BADAN PEMERIKSA KEUANGAN REPUBLIK INDONESIA - Baroroh Shofiati (2021)
This study aims to understand the role of investigative auditors in digital technology transformation to seek, find, and evaluate when there are indications of fraud occurring in Indonesia. Especially in the investigative audit process carried out by BPK auditors in the transformation of digital technology which is growing very rapidly to find out the role of auditors in the current digital era. This research method uses phenomenological qualitative research using primary data that comes directly from the investigative auditors of BPK RI. The results of the study show that the audit process used before the existence of digital auditor technology is still having difficulties in finding, finding and evaluating the documents to be checked due to obstacles in getting the documents to be acquired. With the development of technology and nowadays all humans use technology as a tool in transactions, auditors need special skills and learn related to computer-based examinations or digital technology in analyzing data in the form of databases.